Optical biosensing on a smartphone handset: Non-spectroscopic sensing platform based on retroreflection - Kim, Ka Ram; Chun, Hyeong Jin; Lee, Kyung Won; Jeong, Kwan Young; Yoon, Hyun C. (23rd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2019, 2019)
In this study, we demonstrated a smart handset-based retroreflective optical biosensing and Android application package for point-of-care testing. Briefly, a sedimentation property of an optical probe and organized inverting steps of the microchip were systematically combined to acquire the wash-free immunoassay procedure on the smart handset. Also, the retroreflective optical signal can be registered on a miniaturized optical gadget with the help of Android application for image processing.
Keywords: Android applications; Optical bio-sensing; Optical probe; Optical signals; Point-of-care testing; Retro reflection; Spectroscopic sensing; Optical gadget on smart handset; Retroreflection; Wash-free immunoassay